Augmented Reality Learning Media with Ethnomathematic Approach to Grow Students' Mathematics Learning Motivation - Rohim, Dhina Cahya; Hana, Fida Maisa; Manggalastawa, Manggalastawa; Saharani, Safira; Himayati, Ade Ima Afifa (JTAM (Jurnal Teori dan Aplikasi Matematika), 2024)
The efforts that can be made to increase learning motivation are through the use of learning media integrated with current technology with a culture-based approach that students often find in everyday life. The purpose of this study was to describe the importance of AR in mathematics learning, the use of technology in ethnomathematics, and the effects of AR in fostering student learning motivation. This research method is Systematic Literature Review (SLR) with the PRISMA (Preferred Recording Items for Systematic Review and Meta-analysis) technique. The article search process uses a database from international journals indexed by Scopus and found 287 articles. Then a feasibility study was carried out according to the specified criteria so that 18 final articles were obtained. The results of the study showed that: (1) the use of AR in mathematics learning is very important because it has a positive impact such as improving learning outcomes, increasing learning motivation, improving the quality of learning, creating fun learning, improving learning experiences and improving creative thinking skills; (2) Cultural integration combined with technology provides benefits, namely learning becomes interesting so that it can foster student learning motivation, the form of integration between AR technology and ethnomathematics can be in the form of developing interactive learning media, modules or android-based media; and (3) Several studies using AR-based learning media have provided significant results in increasing students' learning motivation.